Effects of mobility matrices completeness on component-based transfer path analysis methods with and without substructuring applied to aircraft-like components. (17th March 2023) - Prenant, Simon; Padois, Thomas; Rolland, Valentin; Etchessahar, Manuel; Dupont, Thomas; Doutres, Olivier
Abstract: Structure borne noise induced by vibrating systems is considered as a major contribution to the noise generated inside vehicles and can be assessed using Transfer Path Analysis (TPA) methods. Their theoretical formulation requires the mobility of either the vibrating system, the receiving structure or the assembly of the two components according to all Degrees of Freedom (DoFs). However, rotational and in-plane DoFs cannot be measured easily and their determination may result in a more complex experimental set-up or an increase in measurement uncertainties. The need for assessing the full mobility matrices thus deserves to be investigated. In this work, the robustness of multiple TPA methods dedicated to the design and validation phases of aircraft light equipment is investigated numerically according to the mobility matrices completeness and by considering several configurations of assemblies (i.e., different active source properties, different numbers of contact points). Numerical models have been developed to simulate a source with controlled vibratory behavior and the spatial averaged mean-square velocity on the receiving structure is used as an objective indicator of the method's robustness. For proper predictions accuracy, it is shown that the required completeness should account for the terms of highest amplitude and thus depends on the (i) TPA method, (ii) active behavior of the source and (iii) coupling configuration. A completeness involving all the DoFs is generally required for TPA methods based entirely on the mobility of the decoupled components. Otherwise, the omission of rotational or in-plan DoFs could be suitable for TPA methods based on the mobility of the assembly. Highlights: All Degrees of Freedom (Dofs) are not required for accurate predictions provided by the Transfer Path Analysis (TPA) methods. The required Dofs depend on the TPA method considered and on the active and passive dynamic behavior of the structures. Component-Based TPA (CB-TPA) without Dynamic Substructuring (DS) methods only requires the consideration of the translational Dofs. Aeronautical structures may be characterized considering only a quarter of the Dofs for accurate predictions provided by the CB-TPA methods with DS.